Sizing and analysis of a stand-alone photovoltaic and wind system - Ahmed Abdulle, Yahye (2021)
This project discusses the sizing process of a stand-alone hybrid Photovoltaic (PV) and Wind system that will be used at a house located in Hodan, Mogadishu, Somalia. The development of the system is intended to reduce the use of non-renewable energy sources and the causes of major pollution. It is important to establish renewable energy in rural areas where the availability of fuel is costly for grid expansion. Wind energy systems are becoming increasingly accepted, more cost-competitive than conventional energy systems. A photoelectric generation system can be paired with other renewable energy sources such as wind turbines with the benefit of being a powerful summer and winter, day and night with best output during this time when PV energy is reduced (usually in winter and night), and vice versa. However, to use this system there are several factors that need to be focused on. One of the factors is sizing, this is a major factor that needs to be focused because if there is a mistake during calculations there is a probability that the outcome of the design system will not be able to supply enough energy required by the load. Firstly, a hybrid PV and wind system are sized according to the house’s electrical load requirement. Secondly, the performance of the system in terms of energy and cost is analysed. Thirdly, the optimum configuration of the hybrid system is identified. First, the system is designed to generate power 100% from the PV, then 100% from the wind. During the hybrid system sizing, the total energy is split into two halves. One half (50%) of the energy required from the load is received from the PV system. While the other half (50%) is received from the wind system. Eventually, the result found was compared and analysed which is obtained after sizing the system. After comparing and analysing the system, the PV system was best according to less cost than the other systems and cost estimated is RM37,924.43 ($9,481.11).